Pengaruh Iklim Sekolah dan Komitmen terhadap Kinerja Guru Melalui Kepuasan Kerja di SMA Se-Kecamatan Sungai Gelam - Dika, Muhammad Arya; Firjatullah, M. Habi; Pratama, Robin; Idrus, Ali (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of school climate and commitment on teacher performance through job satisfaction. School climate and commitment are considered important for improving teacher performance. The quality of teacher performance influences the quality of educational outcomes. The research method used in this research is a quantitative approach technique. The sample was 60 teachers, the sampling technique used was total sampling, and the entire group of teachers was used as the population. Descriptive statistical tests, normality tests, linearity tests, and hypothesis tests are data analysis techniques used in this research. The results of this research show that school climate and commitment can improve teacher performance, so this research focuses on how teachers can improve their performance through school climate and commitment. Meanwhile, job satisfaction as a mediator variable has no influence on the commitment variable on teacher performance.